1998
DOI: 10.1177/082585979801400203
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care at Home: Reflections on HIV/AIDS Family Caregiving Experiences

Abstract: This study explored the day-to-day experiences of family members providing care at home for their dying loved one with HIV/AIDS. In-depth interviews with seven caregivers were analyzed using grounded theory qualitative methods. A conceptualization of the family caregiving experience portrays HIV/AIDS caregiving as an intense, emotional, and powerful experience filled with pride and enrichment, and conversely, with anger and disillusionment. Findings reflected a significant need for interventions designed to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
3
42
0
1
Order By: Relevance
“…For example, it is possible that caregivers who experience more role overload subsequently pull away from their social network members, shrinking their social world to focus exclusively on the PLHA. 17 Future studies should seek to follow the changes in reported overload over the course of the caregiving relationship, especially considering that disease progression can increasingly strain the caregiver/PLHA relationship. Also, measurements of disease severity, in terms of symptoms and complications experienced by PLHA and their seropositive caregivers could be important predictors of caregivers’ perceived role overload.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that caregivers who experience more role overload subsequently pull away from their social network members, shrinking their social world to focus exclusively on the PLHA. 17 Future studies should seek to follow the changes in reported overload over the course of the caregiving relationship, especially considering that disease progression can increasingly strain the caregiver/PLHA relationship. Also, measurements of disease severity, in terms of symptoms and complications experienced by PLHA and their seropositive caregivers could be important predictors of caregivers’ perceived role overload.…”
Section: Discussionmentioning
confidence: 99%
“…14,28 For the most part, these caregivers reported that the help received influenced their coping in a positive way. This finding is somewhat contrary to previous research that has exposed some of the problematic issues that home-based caregivers can face with the healthcare system and its providers.…”
Section: The Caregiver's Sense Of Securitymentioning
confidence: 96%
“…26 As more and more of the responsibility for care of the dying is placed on family caregivers, there is growing concern about their ability to cope with the demands of caregiving. 27,28 Some research has examined the strategies that family caregivers of patients with cancer use to cope with such demands. Hull, 29 for example, conducted interviews with 14 family caregivers of cancer patients and found that creating windows of time for themselves, engaging in social comparison, and using cognitive reformulation helped caregivers cope with and minimize the stress of caregiving.…”
mentioning
confidence: 99%
“…Its focus, however, is on adult children and the article is drawn from a US-based study. Another work on HIV/AIDS parenting is that of Stajduhar (1998) that makes reference to mothers' experiences in a study on family caregiving situations. There has, however, been a paucity of similar research done on the African continent.…”
Section: T Meyiwamentioning
confidence: 99%